2018
DOI: 10.1002/14651858.cd010859.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy laser photocoagulation for diabetic macular oedema

Abstract: Monotherapy laser photocoagulation for diabetic macular oedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 62 publications
1
22
0
2
Order By: Relevance
“…[1][2][3][4][5][6] SMPL does not induce protein coagulation, and, therefore, prevents formation of retinal scars and tissue damage. 1,7 Even if SMPL has proven to be an effective treatment for diabetic macular edema (DME), in terms of visual function improvement/stabilization and macular thickness decrease, 3,4,[8][9][10][11][12][13][14][15] the exact mechanism of action is still under investigation. Retinal pigment epithelium (RPE) has been considered the main target with the consequent release of "heat shock proteins" (Hsps), in particular Hsp 70.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] SMPL does not induce protein coagulation, and, therefore, prevents formation of retinal scars and tissue damage. 1,7 Even if SMPL has proven to be an effective treatment for diabetic macular edema (DME), in terms of visual function improvement/stabilization and macular thickness decrease, 3,4,[8][9][10][11][12][13][14][15] the exact mechanism of action is still under investigation. Retinal pigment epithelium (RPE) has been considered the main target with the consequent release of "heat shock proteins" (Hsps), in particular Hsp 70.…”
Section: Introductionmentioning
confidence: 99%
“…Die Fachinformation des Dexamethason-Implantats macht darauf aufmerksam, dass die "Erfahrungen bezüglich der Wirksamkeit und Sicherheit wiederholter Verabreichungen für DMÖ" nicht über "mehr als sieben Implantate" hinausgingen [232]. Für Triamcinolon wurde beobachtet, dass die Wirkung des Steroids in der wiederholten Behandlung nachlassen kann [234] In den historischen ETDR-Studien erwies sich die Therapie mittels Laserkoagulation v. a. in der Situation eines klinisch signifikanten Makulaödems als wirksam [235], da sie eine Verringerung der Verschlechterung um mindestens 2 Zeilen gegenüber dem Spontanverlauf erreichte [36]. In den nachfolgenden Studien des DRCR.…”
Section: 1-2 Ivom-therapie Mit Steroidenunclassified
“…Vorerst sprechen die fehlenden Wirksamkeitsdaten, die Belastung der Patienten und die Wirtschaftlichkeit auch gegen eine Ausweitung der IVOM-Therapie auf die Patienten ohne foveale Beteiligung. Somit bleibt die fokale Laserkoagulation hier die sinnvolle Therapieempfehlung, insbesondere wenn die Kriterien eines klinisch signifikanten Makulaödems gegeben sind [36]. [44,200].…”
Section: Therapiewahl: Diabetisches Makulaödem Ohne Foveale Beteiligungunclassified
“…[ 4 5 7 9 12 37 ] A recent Cochrane review concluded that at 1–3 years of follow-up, MLP improved the chances of DME resolution and decreased the chances of visual loss compared to the natural history. [ 38 ] Patients with persistent DME are usually retreated with MLP at 4-month intervals. On average, patients received 3–4 MLP treatments.…”
Section: Continuous Wave Macular Laser Photocoagulation Monotherapy Amentioning
confidence: 99%